Kepercayaan kepada Manajer Waqf: Sebuah Kajian tentang Teori Pengambilan Keputusan Wakaf - Nelly Nailatie Maarif (JURNAL INDO-ISLAMIKA, 2017)
This paper argues that trust toward nazhir (Islamic charitable endowment/waqf manager) is one of the most important factors in the communication Process of Waqf Decision Making (Proses Pengambilan Keputusan Wakaf) and in motivating people to implement waqf. This article suggests leading this trust toward nazhir to be an additionally theoretical contribution to a Five Stage Decision Making Processs conceptualized by Philips Kotler, Gary Amstrong, Jagdish N. Sheth, Banwari Mittal, and Bruce I. Newman. They propose: Problem recognition, searching for information about customers’ needs, alternative evaluation, purchase, and post purchase experience. This paper bases the just above-mentioned argument on the responses of interviewees and the views of the panelists of Focus Group Discussion of this study. They agree to say that communication surrounding the trust toward nazhir is a very important role in stimulating people to perform waqf.